Efek Proteksi Ekstrak Etanol Stichopus hermanii Terhadap Jumlah Limfosit pada Tikus yang Terpapar Asap Rokok dan Diinduksi Candida albicans - Auliasari Yunanda; Syamsulina Revianti; Isidora Karsini S (Denta Journal Kedokteran Gigi, 2015)
Background: Smoking is associated with oral fungi which can causes oral candidiasis. Stichopus hermanii contains of antioxidant, antifungal and immunostimulating agent. Purpose: To evaluate the protection effect of Stichopus hermanii ethanol extract to lymphocytes amount in Wistar rat with CS exposure and C.albicans infection. Material and Method: This experiment were used post test-only control groups design. We used 42 male Wistar rats and divided into 7 groups. 1st group (saline 0,1mL, fresh air, CMC-Na 0,2%), 2nd group (saline 0,1mL, CS, CMC-Na 0,2%), 3rd group (C.albicans 0,1mL, fresh air, CMC-Na 0,2%), 4th group (C.albicans 0,1mL, CS, CMC-Na 0,2%), 5th group (saline 0,1mL, CS, Stichopus hermanii extract 0,02mg/kgBW), 6th group (C.albicans 0,1mL, fresh air, Stichopus hermanii extract 0,02mg/kgBW), 7th group (C.albicans 0,1 mL, CS, Stichopus hermanii extract 0,02mg/kgBW). Wistar rats has been infected by C.albicans for a week, exposed by CS for 8 weeks, and application of Stichopus hermanii extract for 8 weeks period. Furthermore, Wistar rat has been euthanized after 8 weeks of experiments. The amount of lymphocytes was counted through peripheral blood smear method using Diff-count under light microscope with 1000 times magnification. Data were collected and analyzed using Kruskal-Wallis test and Mann-Whitney test. Result: CS exposure and C.albicans infection group can decreaselymphocytes amount. Suplementation groups with Stichopus hermanii extract can increase lymphocytes amount. Conclusion: Supplementation with Stichopus hermanii extract has protective effect to stimulate lymphocytes proliferation in Wistar rat after CS exposure and C.albicans infection.